Indonesians’ perceptions of fully and hybrid English brand names: A survey-based study - Moehkardi, Rio Rini Diah; Muliawati, Nabila; Kurniawan, Hasyim (Universitas Ahmad Dahlan, 2025)
Globalization demands wider use of foreign languages, especially English, on brand names, even for local products. This research aimed to understand how Indonesians perceived the use of English when naming local products and whether there was a feeling of being dominated. It contributes to the study of public perception of foreign languages on brand names. The study used two online surveys to examine perceptions of the brand naming practice, including its formations, meanings, and potential purposes. The first survey aims to select the 15 most familiar brand names out of 30 data points. The second survey, consisting of seven 5-scale Likert items and two open-ended questions, aims to measure the participants' perceptions of the 15 brands. The Likert items generated a mean of 72.08%, indicating that most respondents agree with the statement in each item. The structural equation modeling result shows that English skills have a significant and positive direct impact on perception at .16 (p < .01, 1-tailed), while age shows a negative direct impact at -.27 (p < .01, 1-tailed). Education, on the other hand, has a significant indirect effect on perception (p < .05, 1-tailed) as it affects English skills at .18 (p< .01, 1-tailed). Instead of feeling dominated, the respondents felt that using English is a negotiation to employ English as a creative tool for commercial purposes without losing the sense of nationalism for not using Bahasa Indonesia in the brand names.